Serial dependence of facial identity for own- and other-race faces. Issue 9 (September 2022) - Turbett, Kaitlyn; Jeffery, Linda; Bell, Jason; Digges, Andrew; Zheng, Yueyuan; Hsiao, Janet; Palermo, Romina
It is well established that individuals are better at recognising faces of their own-race compared with other-races; however, there is ongoing debate regarding the perceptual mechanisms that may be involved and therefore sensitive to face-race. Here, we ask whether serial dependence of facial identity, a bias where the perception of a face's identity is biased towards a previously presented face, shows an other-race effect. Serial dependence is associated with face recognition ability and appears to operate on high-level, face-selective representations, like other candidate mechanisms (e.g., holistic processing). We therefore expected to find an other-race effect for serial dependence for our Caucasian and Asian participants. While participants showed robust effects of serial dependence for all faces, only Caucasian participants showed stronger serial dependence for own-race faces. Intriguingly, we found that individual variation in own-race, but not other-race, serial dependence was significantly associated with face recognition abilities. Preliminary evidence also suggested that other-race contact is associated with other-race serial dependence. In conclusion, though we did not find an overall difference in serial dependence for own- versus other-race faces in both participant groups, our results highlight that this bias may be functionally different for own- versus other-race faces and sensitive to racial experience.